Semistrict G-Preinvexity and Optimality in Nonlinear Programming. (7th May 2013) - Peng, Z. Y.; Lin, Z.; Li, X. B.
Abstract : A class of semistrictly G -preinvex functions and optimality in nonlinear programming are further discussed. Firstly, the relationships between semistrictly G -preinvex functions and G -preinvex functions are further discussed. Then, two interesting properties of semistrictly G -preinvexity are given. Finally, two optimality results for nonlinear programming problems are obtained under the assumption of semistrict G -preinvexity. The obtained results are new and different from the corresponding ones in the literature. Some examples are given to illustrate our results.